Design and Implementation of a Stock Purchase System for Printing Businesses Using the Waterfall Method - Ginting, Mega Henia Br; Lee, Francka Sakti (Journal of Information System and Informatics, 2025)
Efficient stock availability is essential for the seamless operation of business processes within a company. However, stock management often encounters several critical challenges, including discrepancies between warehouse inventory and logbook records, as well as mismatches between ordered and received quantities. These issues frequently lead to overstocking or stockouts overstocking increases operational costs and risks quality degradation or expiration of goods, while stockouts disrupt sales and customer service. To address these challenges, this study proposes the design of a stock purchasing management application aimed at optimizing inventory tracking and enhancing operational efficiency within a printing shop. The system is developed using the Waterfall methodology, a structured software development model that helps minimize errors throughout the design process. To validate the system's functionality, black box testing is employed, ensuring that the application performs as intended. The resulting application offers an effective solution to stock management issues, reducing inventory imbalances and supporting more efficient business operations.